Remediation of Organic Pollutants Tofu Liquid Waste Anaerobic - Aerobic Biofilter Combination of Media Phytoremediation Plastic Bottle With Fish For Life Media - Efendi, Sopian; Hasbi, M.; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in September-December 2013 in the tofu factory which is located on Jl . Build Kubang Kingdom Village Tarai Mining District of Kampar district in Riau Province . The purpose of this research is to improve the performance of the biofilter process mediated by a combination of plastic bottles in the phytoremediation of organic pollutants decrease ( BOD and COD ) in waste water out to below the quality standard according PerMenLH No . 15 of 2008 . Results of combination treatment anaerobic - aerobic reactor with fitorediasi of media can reduce BOD levels during the observation with an average of 143.44 mg / l with an average effectiveness of 90.50 % , and for COD can be decreased to 197.46 mg / l with an average effectiveness of 89.74 % . For other parameters also are in accordance with the quality standards that have been established , such as pH 7 , temperature 28 0C , and DO of 3.76 mg / l . While the media processing unit without ( control ) can also reduce levels of BOD and COD , but the effectiveness of processing lower when compared to the unit of media . Where the effectiveness of the average decline during the observation BOD BOD 57.81 % with 661.9 mg / l , and for the effectiveness of COD reached 65.90 % decline in the average COD content of 633.08 mg / l . Tests on fish survival test to know the processed wastewater anaerobic - aerobic reactor combined with phytoremediation of media at the end of the observation has been able to support fish life test . Where to fish monitoring reached 46.67 % , tilapia 70% , and the fish Sepat marsh 86.67 % . While examing to control all kinds of test fish dying until the end of the observation .Keywords : Biofilter, BOD, COD, Waste Water, Plastic Bottle